Disaster and emergency management systems in urban areas - Kapucu, Naim (Cities, 2012)
This article focuses on the factors shaping and constituting governance in urban/metropolitan emergency management. The main focus of the article is the multi-faceted inter-organizational relationships producing shared goals that are practiced at the local level, and specifically within the context of county-level metropolitan emergency management. The article presents a conceptual understanding of the governance concept, a brief summary of related research in the context of emergency management, and an example of the Orlando Metropolitan Area in the State of Florida for practical purposes.